Tanzania Health Financing Policy Notes : The Role of Complementary Financing Mechanisms in Tanzania’s Health Finance Architecture - Ally, Mariam; Piatti-Funfkirchen, Moritz (World Bank, Washington, DC, 2021)
This note reviews the role of domestic financing sources other than general government budget allocations in Tanzania’s health financing architecture. These include funds raised from user fees or cost sharing, reimbursements from the national health insurance fund (NHIF), funds made available from the improved community health fund (iCHF), insurance for workers in the urban informal sector (TIKA), and other private insurance. In Tanzania, these are referred to as complimentary financing mechanisms.